On the methodology and political economy of Galbraithian economics - Gérard Gäfgen (Universität Konstanz, Fachbereich Wirtschaftswissenschaften, 1974)
The paper analyzes J. K. Galbraith's new vision of the economic system of the U.S.A., seen as an example of popular institutionalist thinking. Such a critique seems important because of Galbraith's claim to a closed and complete doctrine ana because of the growing influence of his vulgarized economics. An examination of his methods discovers deficiencies of the systemic approach, obscurities in concept formation, arbitrary formulations of behavioral theories, purely persusive modes of argumentation and techniques of immunization against contrary evidence. An analysis of his system of political economy shows that it lacks a genuine theory of the state and a truly consistent explanation of inequalities of power. So his programme of reforms and of measures of economic policy rests upon rather weak methodological and theoretical foundations. – – Als eln Beispiel popularisierenden Institutionalismus wird J. K. Galbraith' jüngste Gesamtschau des Wirtschaftssystems der U.S.A. einer kritischen Analyse unterzogen. Die Bedeutung einer Kritik ergibt sich aus Galbraith' Anspruch auf eine geschlossene und vollständige Doktrin sowie aus dem Einfluß, welchen diese neue Art von Vulgärökonomie zu gewinnen scheint. Die Untersuchung seiner Methoden ergibt Mängel der systematischen Totalbetrachtung, Unklarheiten der Konzeptualisierung, Willkürlichkeiten bei der Aufstellung von Verhaltenstheorien, rein suggestive Argumentationsstrukturen und Techniken zur Immunisierung der Aussagen gegenüber falsifizierenden Erfahrungen. Inhaltlich zeigt sich, daß in Galbraith' politischer Ökonomie eine eigentliche Staatstheorie ebenso fehlt wie eine konsistente Erklärung der ungleichen Machtbeziehungen. Auch sein Programm von Reformen und wirtschaftspolitischen Abhilfen erweist sich entsprechend als methodisch und theoretisch schlecht abgesichert.
Keywords: 330